Internalizing Early Memories of Shame and Lack of Safeness and Warmth: The Mediating Role of Shame on Depression - Matos, Marcela (2013)
Growing evidence supports the association between early memories of shame and lack of safeness and current shame and depression. Nevertheless, it is unclear whether shame serves as a mediator between such early memories and depressive symptoms.